Pengaruh Ketebalan CPO di Tangki CST terhadap Kadar Kotoran pada PT Perkebunan Nusantara IV Adolina - Rido Sinaga; Jusra Tampubolon (JURAL RISET RUMPUN ILMU TEKNIK, 2024)
This Industrial Internship (Prakerin) was conducted at PT. Perkebunan Nusantara IV Regional II, Plantation Unit, and Adolina Palm Oil Mill (PKS). It focused on analyzing the effect of crude palm oil (CPO) thickness in the Continuous Settling Tank (CST) on CPO impurity levels. The issue raised was the persistent variation in impurity levels in CPO, which is suspected to be influenced by the thickness of the oil layer during the collection process. This study aimed to determine the relationship between CPO thickness in the CST and the resulting impurity levels. The method used was CPO sampling at several oil thicknesses (33–46 cm), followed by laboratory impurity analysis using Gooch Crucible Filter filtration and gravimetric calculations. Data were obtained during the period July 4–11, 2025. The results showed that at a thickness of 45–46 cm, the lowest impurity content was 0.01%, while at a thickness of 33 cm, the highest impurity content was 0.04%. At a thickness of 35 cm, the impurity content was 0.03%, and at a thickness of 40 cm, it was 0.02%. This indicates an inverse relationship between CPO layer thickness and impurity content, where the thicker the oil layer, the lower the impurity content. Therefore, it can be concluded that maintaining a minimum oil thickness in the CST tank of ±40 cm is a crucial step in maintaining CPO quality and ensuring it meets industry standards.